Twenty thousand leagues under the seas - Verne, Jules, 1828-1905.; Butcher, William, 1951- (Oxford : New York : Oxford University Press, 2009)
A nineteenth-century science fiction tale of an electric submarine, its eccentric captain, and undersea world, which anticipated many of the scientific achievements of the twentieth century.
"The extraordinary journeys."
Translation of: Vingt mille lieues sous les mers.
Includes bibliographical references.
Adult.
Adult
Keywords: Submarines (Ships) -- Fiction; Underwater exploration -- Fiction; Science fiction; Sea stories; Submarines -- Fiction; Underwater exploration -- Fiction; Science fiction; Sea stories